1992
DOI: 10.1002/jctb.280530309
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature on fermentation kinetics of waste sulphite liquor by Saccharomyces cerevisiae

Abstract: The optimum operating temperatures for the maximum production of ethanol and the maximum utilization of substrate in batch fermentations of a waste sulphite liquor (WSL) as well as a synthetic medium using Saccharomyces cerevisiae were determined. The fastest consumption of substrate resulting in the shortest fermentation times of 13 h and 45 h was achieved at 35°C and 30°C for the synthetic medium and the WSL, respectively. The concentrations of ethanol in the two media were also maximum under these condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…But temperature tolerance for growth of yeast and fermentation is strongly strain dependent (Rousseau et al, 1992). In the honey wine fermentation, ethanol production was high at 28ºC upto 6 days.…”
Section: Interaction Of Factors and Honey Wine Fermentationmentioning
confidence: 99%
“…But temperature tolerance for growth of yeast and fermentation is strongly strain dependent (Rousseau et al, 1992). In the honey wine fermentation, ethanol production was high at 28ºC upto 6 days.…”
Section: Interaction Of Factors and Honey Wine Fermentationmentioning
confidence: 99%
“…Bajpai and Margaritis (1986) also studied the effect of temperature of medium on the ethanol production by the immobilized Zymomonas mobilis cells during continuous fermentation and found maximum ethanol productivity and activity at 37°C. Rousseau et al (1992) explained the effect of temperature on fermentation kinetics of waste sulfite liquor by S. cerevisiae for bioethanol production and found that the fastest consumption of substrate resulting in the shortest fermentation times of 13 and 45 h was achieved at 35 and 30°C for synthetic medium. Cazetta et al (2007) stated the effect of temperature and sugar concentration on ethanol production by molasses and found that the temperature 30°C was the most favorable for production process.…”
Section: Effect Of Temperature Variations On Bioethanol Productionmentioning
confidence: 99%
“…Subsequently, it was fermented under different temperatures for different time duration. Fermentation liquor was taken and the alcoholic concentration was measured (Rousseau et al, 1992). The results are shown in Table 3.…”
Section: Determination Of the Optimal Conditions For The Alcohol Fermmentioning
confidence: 99%